Sickle cell disease in pregnancy – a rare condition with detrimental outcome: a case report - Nik Sumayyah NMN,; Kalok A,; Nagandla K,; Mohamad Nasir Shafiee, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Sickle cell disease (SCD) in pregnancy is uncommon in Malaysia. We present a case of sickle cell disease in pregnancy with maternal and fetal complications. The patient presented with acute pain crisis and hemolysis in the third trimester. Despite thromboprophylaxis, she developed deep vein thrombosis. The pregnancy was further complicated by severe pre-eclampsia and intrauterine growth restriction which require preterm caesarean section. The baby was admitted to Neonatal Intensive Care Unit due to prematurity and low birth weight. Multidisciplinary approach in managing pregnant patient with SCD is essential in achieving good obstetrics outcome.